A biostimulation-based accelerated method for evaluating the biodegradability of polymers. (November 2020) - da Silva, Schana Andréia; Hinkel, Eduarda Wolf; Lisboa, Thainá Caetano; Selistre, Victória Viana; da Silva, Ana Julia; da Silva, Luiza Oliveira Ferrasso; Faccin, Débora Jung Luvizetto; Cardozo, Nilo Sérgio Medeiros
Abstract: The high cost and long duration of the existing standard tests, such as ASTM D5338 and ISO 14855, represents an important drawback in evaluating the biodegradability of polymers. This works presents a new accelerated method for this purpose, based on the use of a Bartha respirometer and biostimulation with yeast extract. The new method was applied to microcrystalline cellulose (MCC), low density polyethylene (LDPE), poly(3-hidroxybutyrate) (PHB), poly(lactic acid) (PLA), poly(vinyl alcohol) (PVOH), polypropylene (PP) and poly(ethylene terephthalate) (PET). The results obtained with these polymers were consistent with those of the standard methods in terms of differentiating biodegradable and non-biodegradable polymers and relative order of biodegradation extent. Besides, a significant reduction of test duration was achieved (from 45 to 110 days with ASTM D5338 or ISO 14855 to 28 days). These results corroborate the potential of the proposed method as a fast test for assessment of biodegradation of polymeric materials. Highlights: A novel accelerated method to evaluate the polymer biodegradation is presented. The method employs Bartha respirometers and biostimulation with yeast extract. Being easy to perform, it showed reduced duration and cost versus standard methods. Seven assayed polymers efficaciously differentiated in terms of biodegradability. Relative order of biodegradation extent consistent with the standard methods.